COVID-19 infection and high intracoronary thrombus burden (2020)
Coronavirus 2019 (COVID-19) is an acute respiratory disease that has rapidly spread around the world and been declared a global pandemic by the World Health Organization. Emerging evidence demonstrates a strong association with a prothrombotic state and we present the first patient admitted with COVID-19 and an inferior ST-segment elevation myocardial infarction (STEMI) with evidence of high intracoronary thrombus burden. We review the mechanism of the high thrombus burden, which may be driven by the significant cytokine storm, endothelial dysfunction, increase risk of coronary plaque rupture and hypercoagulability.